2020
DOI: 10.18844/cjes.v15i2.4647
|View full text |Cite
|
Sign up to set email alerts
|

Relative effect of animated and non-animated powerpoint presentations on physics students’ achievement

Abstract: This paper determined the relative effect of animated and non-animated powerpoint (PPT) presentations on students’ achievement in physics. A non-equivalent group quasi-experimental research design was adopted for the study, using a sample of 88 senior secondary two students drawn from secondary schools in Nsukka Local Government Area of Enugu State. A 30-item multiple-choice Physics Achievement Test (PAT) was used for data collection. The instrument was both face and content validate. The internal consistency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Ugwuanyi et al (2019b) found that powerpoint presentation had a significant effect on students' achievement in physics and mathematics. Ugwuanyi et al (2020b) found that animated powerpoint presentation (PPT) significantly enhanced the achievement of students in physics. Ugwuanyi and Okeke (2020) found that computer-Assisted Instruction (CAI) had a significant effect on university students' achievement in physics.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ugwuanyi et al (2019b) found that powerpoint presentation had a significant effect on students' achievement in physics and mathematics. Ugwuanyi et al (2020b) found that animated powerpoint presentation (PPT) significantly enhanced the achievement of students in physics. Ugwuanyi and Okeke (2020) found that computer-Assisted Instruction (CAI) had a significant effect on university students' achievement in physics.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Azuka (2013) stated that out of the major factors that influence students' achievement, teacher factors appear prominent. Students' poor performance in physics can be attributed to the lack of teachers' use of innovative teaching strategies in the twenty-first-century classroom (Ugwuanyi et al, 2020b). According to Ugwuanyi et al (2020b), information communication technology (ICT) has a significant impact on students' achievement, especially in this twenty-first century world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruzicka and Milova (2019) found that the use of video analysis in providing feedback has a positive effect on the process of downhill skiing skills acquisition. Ugwuanyi et al (2020) found that animated powerpoint presentation (PPT) significantly enhanced the achievement of students in physics than the non-animated PPT presentation. Ejimonye et al (2020) found that 2D animation technique proved to be significantly effective in enhancing students' motivation in quantitative contents of economics.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…(Danielson, 2011;Ali & Elmahdi, 2001;Fawzi, 2010;Irving, 2015;Damick, 2015;Caldwell, 2007;Baylor & Ritchie, 2002). Technology tools contribute to effective teaching, learning, as well as assessment (Ejimonye et al, 2020a(Ejimonye et al, , 2020bOnah et al, 2020;Ugwuanyi et al, 2019a, b, c;Ugwuanyi et al, 2020aUgwuanyi et al, , 2020bUgwuanyi et al, , 2020cUgwuanyi et al, , 2020d. Modern online classroom response systems if managed very well enhance students' learning through formative assessment.…”
Section: Introductionmentioning
confidence: 99%